Respuesta :

Answer:

x=2    x=-1

Step-by-step explanation:

f(x) = x^2 - X - 2

0= x^2 -x-2

Factor

0 =(x-2)(x+1)

Using the zero product property

x-2 =0   x+1 =0

x=2    x=-1

Answer:

x=2, -1

Step-by-step explanation:

Hi there!

We want to find the zeros of this function: f(x)=x²-x-2

The zeros are the values of x that will make f(x)=0

So that means in order to find the zeros, set f(x) as 0

In that case,

x²-x-2=0

Now let's solve the quadratic equation

We can do it by factoring

-x is the sum of two numbers, while -2 is the product of those two same numbers

Now think: which two numbers add up to -1, but multiply to get -2?

Those numbers are -2 and 1

Now factor the polynomial by FOIL:

(x-2)(x+1)=0

Split and solve

x-2=0

x=2

x+1=0

x=-1

The zeros are x=2, -1

Hope this helps!